The Politics of Development in Botswana A Model for Success? - Picard, Louis A. (Lynne Rienner Publishers, 2023)
Examines the politics of development in Botswana and explores the extent to which the country can serve as a model for other developing states
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mai 2023)
Keywords: POLITICAL SCIENCE / World / African; Politik; Wirtschaft; Sozioökonomischer Wandel; Geschichte; Botswana